Gus Dur's Understanding of Humanity and Pluralism in Defending the Indonesian Chinese Community - Ridwan, Zaenal (Jurnal Fuaduna : Jurnal Kajian Keagamaan dan Kemasyarakatan, 2024)
This paper examines the intricate dynamics of historical interactions between indigenous citizens and Chinese descendants in Indonesia, focusing on the economic and political dimensions of these relationships. It specifically investigates the significant contributions of KH. Abdurrahman Wahid, known as Gus Dur, in advocating for the rights of Indonesian Chinese citizens through the lenses of humanity and pluralism. Utilizing a qualitative methodology, primarily based on library research, the study reveals that during the New Order, discriminatory policies—most notably Presidential Instruction Number 14 of 1967 issued by President Soeharto—imposed severe restrictions on the cultural and religious practices of Chinese Indonesians. In contrast, Gus Dur emerged as a key proponent of democracy, justice, and human rights, championing freedom of expression and the right to worship according to individual beliefs. His pluralistic and humanitarian perspective played a vital role in defending the rights of Chinese descendants in Indonesia. Ultimately, this study underscores the significance of Gus Dur's legacy in the ongoing struggle for equality and human rights within the context of Indonesia's diverse population.